2017
DOI: 10.31289/agrica.v10i2.924
|View full text |Cite
|
Sign up to set email alerts
|

Risiko Usahatani Bawang Merah di Kabupaten Bantul

Abstract: Penelitian ini bertujuan mengukur risiko produksi dan risiko pendapatan usahatani bawang merah di Kabupaten Bantul serta faktor-faktor yang mempengaruhinya, dan mengetahui perilaku petani terhadap risiko usahatani bawang merah di Kabupaten Bantul dan faktor-faktor yang mempengaruhinya. Penelitian dilakukan terhadap 60 petani bawang merah di Kabupaten Bantul. Metode penelitian yang digunakan untuk mengukur risiko produksi dan pendapatan menggunakan nilai koefisien variasi (CV), dan perilaku petani terhadap risi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 1 publication
5
16
0
8
Order By: Relevance
“…Meanwhile, the use of NPK fertilizer is small and is still less than the recommended limit (300 kg/ha), with an average of 200.1 kg/ha. This study is in accordance with research carried out by (Lawalata, 2017;Nikmah et al, 2013). However, it is not in accordance with the research of Battese (2005), and Ogunniyi (2015), which stated that NPK fertilizer had no effect on rice farming activities.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Meanwhile, the use of NPK fertilizer is small and is still less than the recommended limit (300 kg/ha), with an average of 200.1 kg/ha. This study is in accordance with research carried out by (Lawalata, 2017;Nikmah et al, 2013). However, it is not in accordance with the research of Battese (2005), and Ogunniyi (2015), which stated that NPK fertilizer had no effect on rice farming activities.…”
Section: Resultssupporting
confidence: 93%
“…However, the average use is still very poor, especially in the plant rearing phase. The results of this research are in accordance with a study conducted by (Tiedemann & Latacz-Lohmann, 2013), and contrary to the (Lawalata, 2017). Meanwhile, the use of NPK fertilizer is small and is still less than the recommended limit (300 kg/ha), with an average of 200.1 kg/ha.…”
Section: Resultssupporting
confidence: 90%
“…This is contrary to the situation in the rainy season. According to Lawalata (2017), in the rainy season with high rainfall intensity will cause humid conditions on agricultural land, so the risk value of shallot production obtained is higher compared to the dry season. Resmayeti Purba (2014) revealed that the optimum shallot production is affected by the growing season.…”
Section: F Shallot Farming Risk Analysismentioning
confidence: 99%
“…Related to those matters, in carrying out shallot farming, it is highly recommended to pay attention to the combination of the use of both quantity and price inputs in order to achieve maximum output. Lawalata (2017) adds that production risk and income risk can be reduced with the efficient use of appropriate inputs.…”
Section: F Shallot Farming Risk Analysismentioning
confidence: 99%
“…Pada kenyataannya, tidak semua petani mampu mengoptimalkan input produksi mereka. Pada penelitian sebelumnya yang dilakukan oleh Lawalata et al (2017) misalnya, produktivitas agregat pada suatu wilayah tidak berbanding lurus dengan produktivitas masing-masing petani. Hal tersebut dikarenakan tidak semua petani efisien secara teknis.…”
Section: Pendahuluanunclassified